'Tabloidization' and the internet age - Lefkowitz, J (2021)
Claims asserting a decline in journalistic values are not new, dating back to the rise of the penny press in the 1830s. With the ascendance of the Internet, however, such claims have proliferated. These assertions, often referenced as a so-called ‘tabloidization,’ have frequently cited an ascension of tabloid values and content, and/or a decline in the values and content traditionally characteristic of ‘quality’ newspapers. The scholarship, however, lacks longitudinal empirical data from before and during the Internet era which supports, refutes, or modifies these allegations, a lacuna which is particularly problematic in view of the pivotal role of journalism in upholding democracy.